Strain effect in surface acoustic wave elements with a piezoelectric acoustic line and sensors based on this effect - Lepikh, Ya.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The results of investigations of strain effect in surface acoustic wave (SAW) elements with a piezoelectric ceramic (PC) acoustic line are presented. The choice of PC material for acoustic line is substantiated. Some recommendations concerning formation of interdigital transducer structures of the SAW element with PC acoustic line are given. For acoustic lines of different thicknesses fixed in cantilever a dependence of sensor responsivity on deforming force load is found. At optimum thickness of the PC acoustic line the sensor responsivity of 70 Hz/N is realized. The results of this work are compared to those obtained for single-crystal acoustic lines by other authors. A design of a pressure sensor with a strain-sensitive SAW element is presented, and some advantages of such sensors are discussed.